Form, Function, and Meaning of Bebasan: The Orality of the Samin in Bojonegoro - Ismatul Khasanah; Sri Endah Tabiati; Khilmi Mauliddian (Bina Nusantara University, 2022)
The research aimed to describe the form, function, and meaning of bebasan as a cultural orality spoken by the Samin in Bojonegoro. The Samin community was a community group residing in Bojonegoro, East Java. Aside from their distinguished language, the Samin was also well-known for its unique orality called bebasan, representing its culture and society. It was deemed significant to document this national tradition as a form of expression spoken based on the habits and behaviours of the Samin community. In a society that upheld the culture of oral traditions, the Samin community had placed bebasan as one of the rules of life that they subconsciously needed to obey. The research employed folklore theory in order to explore and observe the meaning of bebasan as a part of traditional folklore. Folkore was inseparable from the conditions of society and the culture that encompassed it, so it was necessary to comprehend and give meaning to the folklore. A descriptive qualitative method was applied in the research. Data was obtained by recording and documenting the orality spoken within the Samin community. The results reveal that there are six forms of Bebasan which include directives and teachings on how to conduct oneself well in life. It is also observed that bebasan functions as a medium for advice, reminders, and teachings of life, all ingrained in the Samin community.